Effects of fermentation on SDS-PAGE patterns, total peptide, isoflavone contents and antioxidant activity of freeze-thawed tofu fermented with Bacillus subtilis. (30th May 2018) - Lee, Min-Kyoung; Kim, Jin-Kyung; Lee, Sook-Young
Highlights: Reducing sugar and total peptide contents of freeze-thawed tofu increased after 18 h fermentation with B. subtilis . Freeze-thawed tofu was more digestible after 18 h. Isoflavone-aglycone and antioxidant levels of freeze-thawed tofu increased after 12 h and showed the highest level at 36 h. Abstract: To develop a new healthy functional tofu product, the pH, total cell number, SDS-PAGE patterns, contents of reducing sugar, peptide, isoflavones, antioxidant activity and digestibility of freeze-thawed tofu, fermented with Bacillus subtilis for various time periods, were investigated. In SDS-PAGE patterns, the band intensities of 7S and 11S globulins were slightly decreased and new protein bands of lower molecular weight appeared by fermentation for 12 h. After 18 h, the bands of 7S globulin and the acidic subunit of 11S globulin had almost entirely disappeared and the basic subunit band of 11S globulin was fainter. An 18 h of fermentation was thought to be the most desirable, because the contents of reducing sugar, total peptide, and isoflavone aglycones (daidzein and genistein), as well as antioxidant activities and digestibility of freeze-thawed tofu were more increased by the fermentation for 18 h.